Tiny tales : shell quest - Waldo, Steph (Waldo, Steph. Tiny tales., 2021)
"When a little slug finds new friends in the backyard, she notices they look a lot like her ... except they have shells! Maybe a shell is exactly what she needs to fit in--but finding one is a lot harder than it sounds!"--